Theoretical Approach for Micro-Settlement Control in Super-Large Cross-Section Tunnels Under Sensitive Environments - Zhongsheng Tan; Zhengquan Ding; Zhenliang Zhou; Zhanxian Li (Applied Sciences)
The rapid development of urban transportation renovation and transportation networks in China has driven the construction of an increasing number of large-span, large cross-section tunnels under sensitive environments, such as airport runways, critical infrastructure, and high-speed railways. These projects often require strict settlement control within a millimeter-level tolerance range, thus theoretical methods and key technologies for micro-settlement control have been developed. This study first derives a calculation formula for surface settlement associated with large cross-section tunnels and elucidates its correlations with factors such as pipe-roof stiffness, support system stiffness, pipe-roof construction procedures, and groundwater level changes. Theoretical approaches for controlling micro-settlement are introduced, including increasing pipe-roof stiffness, reinforcing the support system, mitigating group pipe effects, maintaining pressure and reducing resistance around the pipe, and controlling groundwater levels. A method is proposed for determining the appropriate stiffness of the pipe roof and support system. The stiffness should be selected from the transition segment between the steep decline and the gentle slope on the stiffness-settlement curves of the pipe roof and the support system. If the stiffness of the pipe roof and primary support combined with temporary support fails to meet the micro-settlement control requirements, an integrated support system with greater stiffness can be adopted. A reasonable pressure-regulating grouting technique for maintaining pressure and reducing resistance around the pipe is proposed. It is recommended that the spacing for simultaneous jacking of pipes be greater than half the width of the settlement trough. For over-consolidation-sensitive strata such as medium or coarse sands, water-blocking measures, including freezing, grouting, or a combination of both, are recommended. For over-consolidation-insensitive strata like gravels and cobbles with strong permeability, water-blocking treatments are generally unnecessary. The proposed theoretical approaches have been successfully implemented in projects such as the tunnel beneath Beijing Capital Airport runways and Taiyuan Railway Station, demonstrating their reliability. The research findings provide valuable insights into surface micro-settlement control for similar projects.